Early modern écologies beyond English ecocriticism - Goul, Pauline; Usher, Phillip John (Environmental humanities in pre-modern cultures., 2020)
Early Modern Écologies' is the first collective volume to offer perspectives on the relationship between contemporary ecological thought and early modern French literature. If Descartes spoke of humans as being "masters and possessors of Nature" in the seventeenth century, the writers taken up in this volume arguably demonstrated a more complex and urgent understanding of the human relationship to our shared planet. Opening up a rich archive of literary and non-literary texts produced by Montaigne and his contemporaries, this volume foregrounds not how ecocriticism renews our understanding of a literary corpus, but rather how that corpus causes us to re-think or to nuance contemporary eco-theory. The sparsely bilingual title (an acute accent on écologies) denotes the primary task at hand: to pluralize (i.e. de-Anglophone-ize) the Environmental Humanities. Featuring established and emerging scholars from Europe and the United States, Early Modern Écologies opens up new dialogues between eco-theorists such as Timothy Morton, Gilles Deleuze, and Bruno Latour and Montaigne, Ronsard, Du Bartas, and Olivier de Serres.